2022
DOI: 10.1038/s41598-022-04865-0
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation and ecotoxicological risk assessment of heavy metals in surface sediments of the Olt River, Romania

Abstract: Heavy metal pollution of river freshwater environments currently raises significant concerns due to the toxic effects and the fact that heavy metal behavior is not fully understood. This study assessed the contamination level of eight heavy metals and trace elements (Cr, Ni, Cu, Zn, As, Pb, Cd, and Hg) in the surface sediments of 19 sites in 2018 during four periods (March, May, June, and October) in Olt River sediments. Multivariate statistical techniques were used, namely, one-way ANOVA, person product-momen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(18 citation statements)
references
References 66 publications
0
18
0
Order By: Relevance
“…To do this, it is proposed to conduct analytical work to identify groups of agricultural producers whose objective performance indicators can lead to their unification with the support of a center of competencies. Various methods of cluster data analysis are used in various fields of scientific research -agricultural breeding [8], medicine [9], ecology [10], archeology [11], in this study, a practical implementation of the hierarchical clustering method in the software product [7] is undertaken.…”
Section: Resultsmentioning
confidence: 99%
“…To do this, it is proposed to conduct analytical work to identify groups of agricultural producers whose objective performance indicators can lead to their unification with the support of a center of competencies. Various methods of cluster data analysis are used in various fields of scientific research -agricultural breeding [8], medicine [9], ecology [10], archeology [11], in this study, a practical implementation of the hierarchical clustering method in the software product [7] is undertaken.…”
Section: Resultsmentioning
confidence: 99%
“…However, am substances, Cr showed the most prominent environmental impact with RQ season, demonstrating the potential risk of Cr on the ecological environme the risk level for each substance was high during the wet season, except Changes in the RQ values of all substances in the wet and dry seasons fo trends, with some substances (Hg, molinate, carbofuran, quinoline) havin ues, however, posing amplified risks at higher tropical levels, on bioacc assessment should, therefore, not be neglected as a factor in gauging the impacts of potential pollutants [2]. The results demonstrated the internal relationships between the metals and indicated that untreated industrial and municipal waste, as well as other geogenic activities, could be the possible sources of these elements [56], thus highlighting the role of anthropogenic and natural activities on heavy metal accumulation in the environment [31,57,58].…”
Section: Potential Risk Assessment For Human Healthmentioning
confidence: 93%
“…Substantial excess 210 Pb activity at the base of the recovered core showed a high sedimentation rate (Table 1). Indeed, the average sedimentation rate determined in BMR was higher compared to other reservoirs in Southeast Asia [47,48]. The reservoir, which has been undergoing serious sedimentation problems since 1984, was still highly degraded until 2018, showing severe erosion and siltation [49].…”
Section: Sediment Chronologymentioning
confidence: 99%